An analysis of the visual representation of redox reactions in secondary chemistry textbooks from different Chinese communities - Chen, X.; de Goes, L.F.; Treagust, David; Eilks, I. (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This study provides an analysis of selected aspects of the intended curriculum related to redox reactions as represented in secondary chemistry textbooks from the People’s Republic of China, with a special view also on Hong Kong, Shanghai, Taiwan, and the Chinese minority in Malaysia. This study reveals how chemistry textbooks deal with visual representations related to redox reactions and whether or not the visualizations provide any indication for the orientation of the intended curriculum, characterized by contexts suggested for chemistry learning. Specific criteria were derived from a literature review of the discussion on different levels of chemical representations and from a total of 346 visual representations related to redox reactions identified and analyzed from the textbooks. Based on the frequencies and levels of visual representations in the textbooks, this study showed that representations in textbooks from the People’s Republic of China mostly focus on the macro and macro-symbolic levels and indicate some aspects of everyday life as well as orientations towards industry and technology. The findings show that the textbook from Taiwan uses multiple macroscopic, submicroscopic, and symbolic representations to illustrate the redox reactions. The textbook from Hong Kong has a strong orientation along the content structure of chemistry, with mostly macro level representations. The textbook from the Chinese minority in Malaysia follows a strong structure-of-discipline orientation with limited visual support.